Aktualisasi Nilai Bela Negara Sebagai Revolusi Mental Santri Dalam Mewujudkan Keutuhan NKRI di Era Pandemi Covid Dengan Pendekatan Coordinated Management of Meaning (CMM) - Hasan Syaiful Rizal; Nurma Yuwita (Universitas Yudharta Pasuruan, 2021)
This study aims to examine the actualization of the value of defending the state as a mental revolution of students in realizing the integrity of the Unitary State of the Republic of Indonesia in the era of the Covid 19 pandemic with the Coordinated Management of Meaning (CMM) approach. CMM focuses on the self and its relationship to others, as well as the interpretation of the meaning of a message. State defense that has been carried out by students in the era of 1945 with the current era is very different. Currently, Indonesia is facing a threat in the form of an invisible enemy attack, namely Covid 19. Therefore, students must be present at the forefront in the form of defending their country. The actualization of the basic values ​​of defending the state as a mental revolution for students is very much needed in the era of the Covid 19 pandemic in order to improve the quality of life and contribute to the fight against the Covid-19 pandemic. Through the actualization of state defense, it is hoped that it will be able to face attacks from the viral phenomenon that threatens the stability of the country. Santri are expected to take an active role in fighting and resolving Covid 19, because santri have moral intellectuals, high militancy, and the spirit of voluntary self-help jihad. This research uses an interpretive-constructivist approach. The methodology used is descriptive qualitative with purposive sampling method in taking the sample. The data collection methods used are in-depth interviews, observation and documentation. The results of this study are in the form of six levels of the value of defending the state of students as a mental revolution in realizing the integrity of the Unitary State of the Republic of Indonesia in the era of the Covid 19 pandemic which has been actualized by students.